Effects of lower limb amputation on the mental rotation of feet - Curtze, Carolin (Springer-Verlag, 2009)
What happens to the mental representation of our body when the actual anatomy of our body changes? We asked 18 able-bodied controls, 18 patients with a lower limb amputation and a patient with rotationplasty to perform a laterality judgment task. They were shown illustrations of feet in different orientations which they had to classify as left or right limb. This laterality recognition task, originally introduced by Parsons in Cognit Psychol 19:178–241, (1987), is known to elicit implicit mental rotation of the subject’s own body part. However, it can also be solved by mental transformation of the visual stimuli. Despite the anatomical changes in the body periphery of the amputees and of the rotationplasty patient, no differences in their ability to identify illustrations of their affected versus contralateral limb were found, while the group of able-bodied controls showed clear laterality effects. These findings are discussed in the context of various strategies for mental rotation versus the maintenance of an intact prototypical body structural description.